Penerapan Footbath Treatment Terhadap Nyeri Post Sectio Caesarea Ruang Adas Manis RSUD Pandan Arang Boyolali - Gusti Artiyani; Maryatun Maryatun; Panggah Widodo (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2024)
Background: Side effects that occur after undergoing surgery are pain reactions felt by the patient, often causing pain in the patient. Treatments commonly used to relieve pain after caesarean section surgery are pharmacological and non-pharmacological treatments. Footbath therapy or foot soaking using warm water is one of a series of postnatal care therapies that can provide a relaxation response, reduce body pain, because it can help release endorphins in the brain which are natural pain relievers and can help improve blood circulation by widening blood vessels. Objective: to find out the results of implementing footbath treatment for post cesarean section pain in the Adas Manis Room at Pandan Arang Hospital, Boyolali. Method: Descriptive using the case study method. Results: The results after application showed changes in pain in both respondents from before application in the moderate pain category and after application in the mild pain category. Conclusion: There was a change in pain in both respondents, footbath treatment could reduce the scale of wound pain after caesarean section.